P251 Level of Interleukin-17 in Inflammatory Bowel Disease and Its relation to disease activity. (30th January 2023) - Menesy, A; Hammad, M; Aref, S; Abozeid, F
Abstract: Background: Inflammatory bowel disease (IBD) is a chronic relapsing inflammatory disorder of the gastrointestinal tract (GIT).It causes progressive structural and functional damage to the GIT epithelium. Chronic inflammation in IBD is characterized by an imbalance in the production of T helper -1 (Th1), Th2 andTh17 cytokines.This imbalance is important in chronic inflammatory process, since the formation of defective immune response to pathogenic agents promotes the recurrence of the disease.Whether interleukin-17A (IL-17A) has pathogenic and/or protective roles in the gut mucosa is controversial.The aim of this study was to detect serum IL-17 levels in IBD patients and its relation to disease activity. Methods: This was a single center cross-sectional study, conducted at hepatology & gastroenterology unit, Mansoura specialized Medical Hospital, Egypt.Patients who were aged 18-65 years and diagnosed either UC or CD based on previous colonoscopy were included.55 patients were UC, 24 patients were CD, 21 patients were control.Patients who were excluded were <15 y, with history of GIT malignancy or any comorbidities affecting kidney, liver, etc.All population were subjected to routine history, physical examination& laboratory investigations including serum IL-17 by ELISA besides CBC, CRP, ESR, Stool analysis, fecal calprotectin. Results: We found that serum IL-17 level was increased significantly among UC ;median (min-max)= 72(21-502), in CD 54.5(25-260) versus control19(14-35) ng/l, P<0.001.However, it was not correlated to the disease activity either Mayo score of UC or CDAI of CD. It showed significant correlation to the extent of inflammation in UC affecting the colon (either proctosigmoiditis or left sided colitis or pan colitis), also to the type of CD (either inflammatory or stricturing or fistulizing) by P<0.05. It was not correlated significantly with any of the IBD activity markers (either CRP, ESR, or fecal calprotectin).Yet there was only negative significant correlation with Hb level (r =-0.28, p=0.005). AUC was significantly differentiating between IBD and control group =0.993 with the best-detected cut off point from curve is 32 yielding sensitivity of 97.5% and specificity of 95.2%, while for discriminating activity of IBD by IL-17 ;AUC of UC and CD =0.56 & 0.65, with sensitivity 52.6% & 61.5% and specificity 58.3% &63.6 % respectively. Conclusion: IL-17 increases in colonic inflammation significantly more than in control group, however its increase is not correlated to IBD activity.